ANDROID-BASED QURBAN ANIMAL SELECTION RECOMMENDATION SYSTEM USING AHP AND SMART METHOD - Rohmad Shobirin; Samsudin Samsudin (UIN Sumatera Utara, 2023)
Currently, technological advancements have undergone incredibly rapid development. Modern technology is capable of contributing to solving various challenges in different sectors, including the field of animal husbandry. Computers have been integrated as tools to perform tasks or identify existing issues, thus determining the suitability of selecting sacrificial animals. Essentially, whether or not an animal is accepted as a sacrificial offering depends on a series of conditions. Therefore, it is crucial to ascertain whether the animal meets the requirements.Based on research findings, the assessment of code P001 is made using criteria such as Animal Weight, Animal Age, Animal Gender, Blindness, Illness, Limping, Emaciation, and Complete Ears. The assessment is conducted according to the SMART method. The final calculated value for the selection of sacrificial animals is 0.61. Based on the weighting of the final value, it can be concluded that animals with a value of 0.61 are recommended for selection.